Pertimbangan Hukum dalam Penyelesaian Sengketa Proses Pencalonan Peserta Pemilihan Umum di Pengadilan - Chika Nadia Pratiwi (Uniku Law Review, 2024)
Elections are a pillar of democracy that not only guarantees the political rights of citizens, but also demands consistent and fair implementation of the law. The purpose of this article is to find out about the regulations governing the Election Participant Nomination Process including its resolution in the event of a dispute and its implementation in the PTUN Decision Number 583/G/SPPU/2023/PTUN.JKT. The research method used in this preparation uses the normative legal method, which is carried out by examining literature or secondary data consisting of primary, secondary, and tertiary legal materials. The results of this study are that Law No. 7 of 2017 has regulated the general election process and MA Regulation No. 5 of 2017 concerning the settlement of election process disputes. In its application in 583/G/SPPU/2023/PTUN.JKT, the plaintiff Aditya has fulfilled the requirements as stipulated in Law No. 7 of 2017, but in the dispute resolution process that occurred was not in accordance with MA Regulation No. 5 of 2017. The conclusion is that the plaintiff's lawsuit was rejected because it contradicted the provisions as stipulated in MA Regulation No. 5 of 2017.